Steven Spielberg interviews - Spielberg, Steven 1946- (University Press of Mississippi, 2019)
More than four decades after the premiere of his first film, Steven Spielberg (b. 1946) continues to be a household name whose influence on popular culture extends far beyond the movie screen. Now in his seventies, Spielberg shows no intention of retiring from directing or even slowing down. Since the publication of Steven Spielberg: Interviews in 2000, the filmmaker has crafted some of the most complex movies of his extensive career. His new movies consistently reinvigorate entrenched genres, adding density and depth. Many of the defining characters, motifs, tropes, and themes that emerge in Spielberg's earliest movies shape these later works as well, but often in new configurations that probe deeper into more complicated subjects--dangerous technology rather than man-eating sharks, homicidal rather than cuddly aliens, lethal terrorism instead of rampaging dinosaurs. Spielberg's movies continue to display a remarkably sophisticated level of artistry that matches, and sometimes exceeds, the memorable visual hallmarks of his prior work. His latest series of films continue to demonstrate an ongoing intellectual restlessness and a willingness to challenge himself as a creative artist. With this new collection of interviews, which includes eleven original interviews from the 2000 edition and nine new interviews, readers will recognize the themes that motivate Spielberg, the cinematic techniques he employs to create his feature films, and the emotional connection he has to his movies. The result is a nuanced and engaging portrait of the most popular director in American cinema history."--Provided by publisher
Includes index
Keywords: Spielberg, Steven -- 1946-; Spielberg, Steven / 1946- / Interviews; Motion picture producers and directors / United States / Interviews; Spielberg, Steven / 1946-; Motion picture producers and directors; United States; Interviews; Interview